The Influence of Product Innovation, Marketing Innovation, and Organizational Climate on The Marketing Performance of Convection MSMES - Tafrikhan Zulqarnain Oase; Audita Nuvriasari (Arthatama: Journal of Business Management and Accounting, 2025)
MSMEs play a crucial role in the Indonesian economy, particularly in providing employment opportunities and fostering regional economic growth. This study aims to analyze the influence of product innovation, marketing innovation, and organizational climate on the marketing performance of conventional MSMEs in Boyolali. This study uses a quantitative, cross-sectional design. The population comprises convection MSME owners and managers in Boyolali Regency, Central Java, with 100 respondents selected through purposive sampling based on specific criteria. Data collection was obtained through questionnaires distributed to respondents face-to-face. The data analysis tool uses multiple linear regression. The results of the study show that product innovation, marketing innovation, and organizational climate have a positive and significant effect on the marketing performance of MSMEs. This research supports the Resource-Based View (RBV) theory, which emphasizes the importance of capabilities and internal resources in improving marketing performance.